Production of potato microtubers by using tissue culture techniques - Sayed Ewase, Alaa El-din; M. Blieblo, Ali (Scientific Journal of University of Benghazi, 2026)
Production of potato microtubers was reviewed here. Microtubers production is an efficient method for obtaining a healthy material, through which the process of potato production is reduced with 3-4 years. In the same time, microtubers have a great importance because they could be produced in any period of the year, they are easy to be transported , handle, store and distribute. Also, their use is rapidly increasing world wide. Many chemicals are used for this process like 2,4-D, Coumarin, Kinetin and others under certain conditions of light and temperature , high sucrose content (90 g/l as a maximum ) and through tissue culture techniques.